Variabilitas Genetik pada Beberapa Varietas Unggul Baru Padi (Oryza sativa L.) Berdasarkan Penanda Morfologi Biji - Ardani, Hanna Qotrunnada; Syafii, Muhammad; Azizah, Elia; Susanto, Untung (UNIVERSITAS LABUHANBATU, 2024)
Rice (Oryza sativa L.) is known to have a very diverse genetic diversity. The target of rice variety improvement is to produce new varieties that have superior traits in accordance with the development objectives in each typological region. This study aims to determine the level of similarity formed in a number of new superior varieties. The method used is descriptive experimental, with 51 treatments, namely new superior varieties, repeated 3 times so that there are 132 experimental units. Each agronomic character observation data was analyzed by clustering using the UPGMA method. The analysis used NTSYS 2.02i and 2.11a software. The results showed that the genetic variability of 51 new superior varieties of rice (Oryza sativa L.) has a similarity coefficient value of 0.81 based on clustering analysis. This shows a high level of similarity of genetic variability, however, the clustering results form 5 main groups with genetic distances ranging from 0.0000 - 0.5593. Keywords: genetic variability, seed morphology, new improved varieties, clustering.